35th AIAA Fluid Dynamics Conference and Exhibit 2005
DOI: 10.2514/6.2005-5269
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Control of Cavity Flow Using Experimental Based Reduced Order Model

Abstract: In our recent work we presented preliminary results for subsonic cavity flow control using a reduced-order model based feedback control derived from experimental measurements. The model was developed using the Proper Orthogonal Decomposition of PIV images in conjunction with the Galerkin projection of the Navier-Stokes equations onto the resulting spatial eigenfunctions. A linear-quadratic optimal controller was designed to reduce cavity flow resonance by controlling the time coefficient and tested in the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 24 publications
4
30
0
1
Order By: Relevance
“…2. It's interesting to notice that the estimate of the state a can be derived directly from pressure measurements by using equation (3.5). A saturation function and a constant scaling factor ct play the same roles in the feedback loop as what have been presented in Caraballo et al (2005). The largest possible scaling factor in this study has been found to be a = 0.265, and the corresponding scaled control is in the form…”
Section: Real Time Control Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…2. It's interesting to notice that the estimate of the state a can be derived directly from pressure measurements by using equation (3.5). A saturation function and a constant scaling factor ct play the same roles in the feedback loop as what have been presented in Caraballo et al (2005). The largest possible scaling factor in this study has been found to be a = 0.265, and the corresponding scaled control is in the form…”
Section: Real Time Control Resultsmentioning
confidence: 71%
“…The increased number of snapshot compared to that (500) used in Caraballo et al (2005) allowed complete convergence of the average turbulent kinetic energy of the flow in the shear layer region. Figure 3 shows how the mean turbulent kinetic energy at different location on the shear layer converges when more than 700 images are used.…”
Section: Pod Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This results in a set of ordinary non-linear differential equations, in which the control input need to be rendered explicit by means of control separation techniques. The use of POD/Galerkin methods has become increasingly popular to handle flow control problems, including control of cylinder wakes [11,26,42], flow separation [19], modeling and control of synthetic jets [27], controller order reduction [3], and cavity flow [5,6,32,46].…”
Section: Introductionmentioning
confidence: 99%